ANALISIS YURIDIS PERGANTIAN NAZHIR OLEH WAKIF PADA PUTUSAN PENGADILAN AGAMA NOMOR 0168/Pdt.6/2018/PA.Pyk - Hidayat, Rahmat; Tiswarni, Tiswarni; Hadi, Sutrisno; Ramadani, Ramadani (Al-muamalah, 2024)
This paper examines the juridical analysis of the change of nazhir conducted by the wakif in the decision of the Payakumbuh Religious Court Number 0168/Pdt.6/2018/PA. Pyk between the Suliki Kewedanan Organization as the plaintiff and the Amanah Islamic Education Foundation as the defendant. The author wants to analyze juridically the change of nazhir carried out by the wakif contained in the court decision, whether it is in accordance with positive law and Islamic law or not. This research is included in the scope of legal research with the primary data source being the Religious Court Decision Number 0168/Pdt.6/2018/PA. Pyk and the results of interviews with the panel of judges who decided the case. The results showed that the case of the waqf dispute was related to the change of nazhir carried out by the wakif and the heirs of the wakif because the previous nazhir did not carry out its functions and duties to manage waqf. The judge's consideration that decided this case included that the Organization was proven not to carry out its duties as a nazhir, the mechanism for changing nazhirs was in accordance with applicable regulations, and nazhir was an organization that was not clear about its AD / ART so it was considered an illegal organization. In terms of Positive Law, the judge's decision cannot be fully justified because some are in line with Law No. 41 of 2004 and BWI regulations and some are not. The decision that is in line with positive law is to reject the plaintiff's claim that the waqf land and its assets are handed back under the management of PWKS because the organization did not carry out the conditions conveyed by the wakif when the waqf pledge occurred. While the inappropriate verdict is the process of changing nazhir which must go through BWI. In terms of Islamic Law, this ruling is appropriate, because a nazhir who cannot perform his duties may be dismissed by the wakif who chooses him, because the wakif has the authority to choose and replace the nazhir he appointed.